OPTIMIZATION OF PHARMACISTS TRAINING BY SOLVING NOT TYPICAL SITUATIONAL TASKS IN "CLINICAL PHARMACY" DISCIPLINE - Купновицька, І. Г.; Клименко, В. І.; Фітковська, І. П.; Белегай, Р. І.; Губіна, Н. В.; Данилюк, О. І.; Вівчаренко, М. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Quality of pharmacist training is largely determined by fullness, systematic, active training in dealing with non-standard, not typical tasks of III level. Solving situational tasks enables students to apply the most rational drug therapy for individual patients based on evidence-based medicine, to select the most effective and safe medicines, adequate dose dosage form and mode of administration, interpret and take into account in clinical practice, clinical features of pharmacokinetics, pharmacodynamics, side effects and interactions of major groups of drugs, considering individual characteristics of the organism, the course of the disease, the presence of comorbidity.